Mapping of Students' Scientific Literacy Skills at Mataram - Gito Hadiprayitno; A Wahab Jufri; Siti Syifa’un Nufus (SEJ (Science Education Journal), 2020)
This study aims to describe the achievement of students’ scientific literacy competencies in Integrated Science subjects. Research subjects were class VIII students at MTsN Mataram in the 2019/2020 academic year. The research method was used descriptive with a qualitative approach. Research sampling technique was purposive sampling. Data collection technique used a written test on the aspects of scientific literacy competence according to PISA 2018. Data analysis were used descriptive, Bivariate Correlation test, and Anova test used software application related. The results showed that the students’ scientific literacy skills in the Integrated Science including very low category (40.5%) with the highest to the lowest achievements in each category a) interpreting data and proving data (15, 4%), b) test and design scientific investigations (13.6%), and c) explain phenomena (11.6%). So, we need more effort to improve and increase students’ scientific literacy skills by integrating aspects of scientific literacy competencies during implementing science learning in schools.